Policy Analysis on Forest and Land Fire Prevention and Management in Jambi Province - M Alfiansyah M Alfiansyah; Hutwan Syarifuddin; Marwoto Marwoto (Rifa'Institute, 2026)
Introduction: Forest and land fires are major environmental problems in Indonesia, particularly in peatland areas of Jambi Province, where fires occur almost every year and cause ecological, social, and economic impacts. Objective: This study aimed to analyze forest and land fire prevention and control policies and determine priority control strategies in Jambi Province using SWOT and Analytical Hierarchy Process (AHP). Method: This study used a descriptive qualitative approach. Data were collected through interviews, questionnaires, and documentation involving stakeholders related to forest and land fire management. SWOT analysis was used to identify internal and external factors, while AHP was applied to determine strategic priorities. Results and Discussion: The results showed that forest and land fires in Jambi Province still occurred annually during 2015–2024, with the highest number of hotspots recorded in 2019 at 3,539 hotspots. SWOT analysis placed the fire control strategy in Quadrant I, indicating that strengths and opportunities could support fire management efforts. The AHP analysis identified strengthening forest fire task forces based on hotspot monitoring technology and early warning systems as the main priority strategy with a global weight value of 0.348742384. Conclusion: Strengthening institutional capacity and utilizing hotspot-based information technology and early warning systems are important strategies for improving forest and land fire prevention and control in Jambi Province